2008
DOI: 10.1056/nejmoa070403
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Red-Cell Storage and Complications after Cardiac Surgery

Abstract: In patients undergoing cardiac surgery, transfusion of red cells that had been stored for more than 2 weeks was associated with a significantly increased risk of postoperative complications as well as reduced short-term and long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
1,095
13
29

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,244 publications
(1,173 citation statements)
references
References 45 publications
36
1,095
13
29
Order By: Relevance
“…Prolonged storage of transfused red blood cells appears to provoke numerous serious postoperative morbidities along with mortality. 26 Exclusion of patients with missing information (the complete-case approach) can also result in substantial bias and underestimate risks of patients because excluded patients may have the highest comorbidities and thus be at highest risk of mortality. To estimate the contribution of this potential bias, we calculated the mortality rates in excluded and included patients and found the rates to be similar.…”
Section: Limitationsmentioning
confidence: 99%
“…Prolonged storage of transfused red blood cells appears to provoke numerous serious postoperative morbidities along with mortality. 26 Exclusion of patients with missing information (the complete-case approach) can also result in substantial bias and underestimate risks of patients because excluded patients may have the highest comorbidities and thus be at highest risk of mortality. To estimate the contribution of this potential bias, we calculated the mortality rates in excluded and included patients and found the rates to be similar.…”
Section: Limitationsmentioning
confidence: 99%
“…4,5 Experimental studies have shown that both hypoxic and nonhypoxic mechanisms may contribute to anemia-induced organ injury and mortality. 3,6,7 The complex nature of the cellular mechanisms involved may explain why anemiainduced mortality is not necessarily improved by therapies which increase blood oxygen content, including red blood cell (RBC) transfusions, 8,9 use of erythropoiesis stimulating agents (ESAs), 10 or hemoglobin-based oxygen carriers (HBOCs). 11 Each of these strategies is capable of increasing blood oxygen content but may not increase tissue oxygen delivery.…”
Section: Résumémentioning
confidence: 99%
“…There is increasing evidence that excessive bleeding requiring transfusions is independently associated with serious perioperative events, such as sepsis, acute respiratory distress syndrome, renal failure, and death. [4][5][6] Surgical causes of bleeding are found in less than 50% of patients undergoing re-operations for bleeding, and it is proposed that microvascular coagulopathy is the most common cause of postoperative hemorrhage. A heparin rebound phenomenon (reappearance of anticoagulant activity after adequate neutralization with protamine) can contribute to this coagulopathy.…”
mentioning
confidence: 99%